The Franklin’s prologue and tale: The idea of change - Dohal, Gassim (Research Journal in Advanced Humanities, 2024)
The Canterbury Tales by Geoffrey Chaucer, written in 1387, chronicles the transformations that the travelers experience. These modifications can come in a wide range of forms and shapes. Among these travelers is the Franklin, whose account includes a list of certain alterations that may be tracked down and examined. I’ll examine how ‘The Franklin’s Prologue and Tale’ handles various kinds of transitions in the debate that follows. After carefully reading this article, readers will understand that transformation in life can take many different forms. It will also provide an opportunity to view other stories from the same viewpoint.